Has the outcome for patients who undergo resection of primary retroperitoneal sarcoma changed over time?: a study of time trends during the past 15 years - Callegaro, Dario; Raut, Chandrajit P.; Ng, Deanna; Strauss, Dirk C.; Honoré, Charles; Stoeckle, Eberhard; Bonvalot, Sylvie; Haas, Rick L.; Vassos, Nikolaos; Conti, Lorenzo; Gladdy, Rebecca A.; Fairweather, Mark; et al. (Annals of surgical oncology, 2021)
This study aimed to investigate changes in treatment strategy and outcome for patients with primary retroperitoneal sarcoma (RPS) undergoing resection at referral centers during a recent period.
Published online: 18 October 2020
Gesehen am 09.09.2021